Analisis Komunikasi Pemasaran di PT. Melia Sehat Sejahtera dalam Menarik Minat Konsumen - Nasution, Abdul Rahman Pais; Dalimunthe, Maulana Andinata; Berutu, Nursadimah (Lembaga Yasin AlSys, 2024)
This research aims to analyze marketing communications implemented by PT. Melia Sehat Sejahtera in an effort to attract consumer interest in its products and services. The research method used involved interviews with the company's marketing managers to gain in-depth insight into the communication strategies that had been implemented. The interview results show that the company has adopted a diverse marketing communications strategy, including an active presence on social media, personal selling, as well as promotional events and collaborations with health influencers. Despite its success in attracting consumer interest, the company is also faced with several challenges, such as intense competition, changing consumer trends, and advertising bans. This research provides an in-depth understanding of PT's marketing communications strategy. Melia Sehat Sejahtera, as well as highlighting the challenges faced in dealing with the dynamics of the health market. The implications of the research results can be used as a basis for developing more effective and adaptive marketing strategies in increasing consumer attractiveness.